The fact checker : a novel - Kelley, Austin, 1973- (Atlantic Monthly Press, 2025)
"It's just a puff piece about a farmer's market, I said to myself. It's not going to kill anyone. It started out like any other morning for the Fact Checker. The piece, "Mandeville/Green," didn't raise any red flags. There were more pressing stories that week at The Magazine-terrorism, war, or some other grave matter-it being 2004 New York City and all. "Mandeville/Green" was a light, breezy look at a local farm called New Egypt, whose Ramapo tomatoes were quickly becoming the summer's hottest produce. At first glance, the story seemed straightforward, but one line made the Fact Checker pause: a stray quote from a New Egypt volunteer named Sylvia making a cryptic reference to "nefarious business" at the farmer's market. "People sell everything here," she's alleged to have said. "It ain't all green." When Sylvia abruptly disappears the morning after an unexpectedly long night with the Fact Checker, he becomes obsessed with finding her. Did Sylvia discover something unsavory about New Egypt or its messianic owner? Is it possible she had some reason to fear for her safety? Or was it simply something the Fact Checker said? Striking the perfect balance of humor, wonder, sadness, and poignancy, Austin Kelley's debut novel takes readers on a quixotic quest from one hidden corner of New York City to another-from an underground supper club in the Financial District to an abandoned-boat-turned-anarchist-community-space on the Gowanus Canal. As the story develops, the Fact Checker begins to question his perception of what's real and what's not. Facts can be deceiving, after all, and if you aren't careful, you might miss the truth right in front of your eyes"--